APLIKASI WEB MOBILE CALON PENERIMA JAMBAN SEHAT BAGI KELUARGA KURANG MAMPU METODE TOPSIS - Guna Yanti Kumala Sari Siregar Pahu; Evi Haryani; Muhamad Muslihudin (Jurnal TAM (Technology Acceptance Model), 2019)
Decision making using multiple attribute has an advantage in determining alternative weight values. In determining to determine the condition of latrines declared healthy or unhealthy using six criteria, including: Knowledge, the number of people using latrines, Institutional Monitoring, Regulations, Cleanliness of Public Facilities, Community Behavior. In this study, to determine healthy latrines, community samples were used in Pringsewu District. The TOPSIS method is applied to determine the priority of unhealthy latrine conditions. The research aims to design a Decision Support System for the feasibility of latrines in public housing in Pringsewu District to realize Pringsewu Open Defecation Free. Testing results are combined with using web mobile to facilitate the Health Office in calculating weight values and following up on the results of calculations as an evaluation material for the service to prepare policy directives to achieve the goal of Open Defecation Free. From the Test Results the system describes the results of calculations and accurate research in accordance with the manual tests conducted. Which alternative 3 has the highest value than the other alternatives while alternative 4 has the lowest value.